Principles in prevention of periodontal diseases: Consensus report of group 1 of the 11th European Workshop on Periodontology on effective prevention of periodontal and peri-implant diseases - Tonetti, Maurizio S; Eickholz, Peter; Loos, Bruno G; Papapanou, Panos; van der Velden, Ubele; Armitage, Gary; Bouchard, Philippe; Deinzer, Renate; Dietrich, Thomas; Hughes, Frances; Kocher, Thomas; Lang, Niklaus P; et al. (Journal of clinical periodontology, 2015)
In spite of the remarkable success of current preventive efforts, periodontitis remains one of the most prevalent diseases of mankind. The objective of this workshop was to review critical scientific evidence and develop recommendations to improve: (i) plaque control at the individual and population level (oral hygiene), (ii) control of risk factors, and (iii) delivery of preventive professional interventions. Discussions were informed by four systematic reviews covering aspects of professional mechanical plaque control, behavioural change interventions to improve self-performed oral hygiene and to control risk factors, and assessment of the risk profile of the individual patient. Recommendations were developed and graded using a modification of the GRADE system using evidence from the systematic reviews and expert opinion. Key messages included: (i) an appropriate periodontal diagnosis is needed before submission of individuals to professional preventive measures and determines the selection of the type of preventive care; (ii) preventive measures are not sufficient for treatment of periodontitis; (iii) repeated and individualized oral hygiene instruction and professional mechanical plaque (and calculus) removal are important components of preventive programs; (iv) behavioural interventions to improve individual oral hygiene need to set specific Goals, incorporate Planning and Self monitoring (GPS approach); (v) brief interventions for risk factor control are key components of primary and secondary periodontal prevention; (vi) the Ask, Advise, Refer (AAR) approach is the minimum standard to be used in dental settings for all subjects consuming tobacco; (vii) validated periodontal risk assessment tools stratify patients in terms of risk of disease progression and tooth loss. Consensus was reached on specific recommendations for the public, individual dental patients and oral health care professionals with regard to best action to improve efficacy of primary and secondary preventive measures. Some have implications for public health officials, payers and educators.